CLINICAL ASSESSMENT OF HYPOTHYROID SYMPTOMS IN DIFFERENT TYPES OF PRAKRITI - Prasuna, V.V.L.; Srinivasulu, Bandari (International Journal of Ayurveda and Pharma Research, 2015)
Ayurveda gives utmost importance to personalized therapy. It upholds individual physiology, pathology, treatment methods and lifestyle adaptations by means of Prakriti (body constitution), Prakriti is the unique psychosomatic temperament of an individual, encompassing the persons physical, functional and behavioural characteristics. Like genetic coding, every individual has a different combination and is therefore a distinct entity. Each and every person is different and their physiological (Agni, Koshta) and pathological manifestations vary accordingly. Each person responds differently though exposed to same stimuli. Lot of research works has been carried out to establish the role of Prakriti in different diseases. In the present study, an attempt is made to evaluate the role of Prakriti in the manifestation of hypothyroidism in different individuals. 100 hypothyroid patients are selected and grouped according to their Prakriti and their clinical features were studied. The group of patients belonging to the same Prakriti have showed similarity in their clinical features. This approach will help in assessing the susceptible clinical features of each Prakriti type and also helpful to take preventive measure in arresting the progression of disease.